An Optimum Way to Evaluate the Performance of Outbound SCM through Process Evaluation - Aruna Kumari C.P; Vijaya Kumar Y (International Journal of Supply Chain Management, 2015)
Today, most of the companies are focusing on cost reduction to ensure that there is an effective supply chain in the organization where performance measurement and metrics are the key parameters which have received the attention of researchers and practitioners recently to use for measurement. To survive in a highly challenging and competitive environment, an efficient and effective way of measuring supply chain performance is a must to improve profitability and efficiency of an organization. There are several performance measures for evaluating the process of Supply Chain Management since it is important to make the system robust. In this paper an attempt has been made to evaluate outbound SCM mainly by focusing the whole process by evaluating the performance measurement parameters and metrics which are involved in the process and keeping the total cost of SCM in control. The performance can be measured in terms of Inventory turnover ratio, logistics cost and linking inventory control methods with respect to total cost of supply chain.